(untitled) (PUBMET, 2023)
In economics, “a public good refers to a service that is made available to all members of a society”. Typically, these services are administered by governments and paid for collectively through taxation. There is an increasing awareness that the free market is creating deep inequalities in access and participation in scholarly communications, even with the transition to open science. It is now time to collectively chart a new course where research outputs are treated as public goods. This is no easy task, as it requires working across countries, domains, and stakeholder communities. This talk will identify the major actions needed to move forward with this vision, and present the activities of the Confederation of Open Access Repositories (COAR), a global organisation of repository initiatives, that are contributing to our collective progress.